Hope movements: Social movements in the pursuit of human development - Séverine Deneulin; Ana C. Dinerstein (University of Bath, Centre for Development Studies (CDS), 2010)
The evaluative framework of Sen's capability approach provides the most robust alternative to utilitarian economics and its income and growth oriented vision of development. However, despite its affirmation of human flourishing as development objective, it does not provide an alternative to economic and social practices which undermine that objective. It therefore needs to engage more with forms of social and political mobilisation, which seek to create an alternative social and economic world more akin to human flourishing and dignity. The aim of this paper is to analyze the role of these social and political mobilizations in development. We argue that they constitute a new type of social movements inspired by 'hope'. That is, following Bloch, they are striving forward to create another world, moved by the anticipatory consciousness of a 'not-yet-become'. We examine two seeming dissimilar social movements: the Zapatistas in Latin America and the Live Simply in Europe. Despite their differences, these movements share common characteristics, which do not fit easily within the category of 'new' social movements, in that they question the existing relation between social movements and development, and intend to offer not simply alternative forms of development but alternatives to development. We propose to name them 'hope movements' so as to better capture what they are and do. We conclude by discussing the significance and implications of the category of hope for development.
Keywords: 330; Bloch; hope; capability approach; development; social movements; social change; Zapatistas; Live Simply